(3EOGQI GdJCejf h GdeNGWQs - (3YQaGJ GHQGgje(B, (3ajGVs ((3YeGf(B:s (3OGQ GdHOGjI(B,s, 2011)
(3CfhGY GdJCejf , Gdgjcd GdJfXjej dTQcGJ GdJCejf h gjcd GdfXGe GdeMGSHj aj gPg GdTQcGJ , SLdGJ TQcGJ GdJCejf h SLd GdJYOjdGJ h GdGdZGAGJ , YedjGJ bSe GdJCejf Ydi GdMjGI I Jchjf GdGehGd h YedjGJ EYGOI GdJGejf , GdMSGHGJ GdNJGejI h GdejRGfjI aj TQcGJ GdJGejf , ebOeI aj GdJQhjL GdJLGQj , CSGSjGJ aj GOGQI GdeUGQa (B.s
Keywords: (3GdCNWGQs; (3GdCNWGQ `` GOGQIs; (3GdEOGQIs; (3GdJCejf ` EOGQIs; (3GdJCejf (B- (3GdHfhcs